Study of FEC at edge node of optical code label switching network - Yu-bao WANG; Shao-yu ZHI (Tongxin xuebao)
The structure block of the optical code label switching network was built,and the design scheme for the forwarding equivalent classes (FEC)was proposed employing OCDM technology which was appropriate for variable packets transmission and allow the label processed in parallel in core node.The overhead between the duration of control bits and the duration of payload was investigated based on the above design scheme.The fixed slot algorithm (FSA) was employed to assemble the incoming packets in the assemble queue,simulation results and analysis were given between the relation of arrival ratio/assemble slot and packets loss ratio.